Value-Based Edupreneurship and Parental School Choice in Islamic Education: A PLS-SEM Analysis: Edupreneurship Berbasis Nilai dan Pilihan Sekolah oleh Orang Tua dalam Pendidikan Islam: Analisis PLS-SEM - Wisnu Uriawan; Deli Purnawan; Muhammad Rahmat Jauhari; Idam Ma'mun; Chaerul Rochman (CV. Media Publikasi Profesional, 2026)
This study aims to examine the influence of edupreneurship strategy on parents’ interest in choosing Nurul Imam Islamic School, Karawang, West Java. The study is important because Islamic schools increasingly face competition and need to develop value-based strategies that integrate service quality, facilities, learning quality, additional services, and institutional branding. This research employed a quantitative explanatory design using a structured questionnaire distributed to [number of respondents] parents or guardians of students. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings show that the proposed edupreneurship model has strong explanatory power, with an R² value of 0.856, indicating that 85.6% of the variance in parents’ interest can be explained by the model. Service quality shows the strongest direct association with parents’ interest, while learning quality provides the largest substantive contribution based on effect size. School facilities also emerge as a key factor, whereas branding and promotion and additional services show limited contribution. These findings imply that Islamic school management should prioritize service improvement, learning quality, and facility development over promotion-based strategies alone. The originality of this study lies in integrating edupreneurship, educational marketing, service quality, and parents’ school choice into one empirical model in the context of Islamic school management.